Une révolution bureaucratique britannique ? - Gales, Patrick LE; Scott, Alan (Una revolución burocrática británica ? Autonomía sin control o « freer markets, more rules »., 2008)
This article originated with a puzzle : how best to account for changes in the behavior of groups, organizations and individuals in Great Britain ? A detailed analysts of what Weber and Polanyi identified as interdependencies between state and market, and of the state's role in creating the market, led to the decision to adapt the notion of bureaucratic revolution put forward by Weber. We argue that the British bureaucratic revolution is reflected in the fact that the state plays an essential role in social change by creating rules and institutions that lastingly orient actors' behavior. The examples of health and local authorities are then used to identify mechanisms that were influential throughout a ten-year period specifically the introduction of competition features (rewards and punishments) and of auditing and inspection. If our interpretation is accurate, the effects of this bureaucratic revolution may well come to be felt in contexts other than Great Britain. (English)
Keywords: 1997-2010; Great Britain - social conditions - 1945-; WEBER, Max, 1864-1920; bureaucratization; economic policy; social goals; socioeconomics

Economie et Rationalite: Apports et limites de l'approche polanyienne. (Economics and Rationality: Contributions and Limits of Polanyian Approach. With English summary.) - Postel, Nicola; Sobel, Richard (Cahiers d'Economie Politique, 2008)
Polanyi analyzes the historical deployment of a "formal" economic science starting from the triptych "market-rarety-instrumental rationality". It reveals this triptych, and the knowledge which is devoted to it, as being a part of a question broader than should analyze a "substantial" economic science being interested in the triptych "need-nature-institution". If we can and must follow Polanyi in his criticism of economism suited to the first triptytic, we have more reserve to accept his solution of substitution, an heterogeneous mixture of naturalism and institutionalism, of essentialism and historicism. The thesis defended in the article is that it is necessary to be more Polanyian that Polanyi himself, and to develop an economy of the practical reason, base of an economic science reintroduced inside social sciences.
Keywords: criticism of economism; formal economy; general economics

Karl Polanyi, le marché et le socialisme - Skornicki (2008)
La société est-elle condamnée à subir les lois du marché ? La publication d'Essais inédits de l'économiste Karl Polanyi permet de redécouvrir le (...)
Keywords: capitalisme; fascisme; marché; socialisme